The self- complementary bow-tie vacant dipole with log periodic characteristic quadband antenna design - et. al., Sunanda Roya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, the diagonally symmetrical pair of modified cross dipole inscribed in a circle with equilateral triangular shaped bow-tie log-periodic characteristic quad band antenna is proposed for wireless energy harvesting application. The suggested quad band antenna is capable of satisfying wider bandwidth for available RF frequency bands including GSM 900 (880 MHz-960 MHz), GSM 1800 (1710 MHz-1880 MHz), 3G (1920 MHz-2300 MHz) and Wi-Fi (2.4 GHz-2.45 GHz) in ambient level. The performance characteristic of the antenna is analyzed in terms of scattering parameter, maximum realized gain, total and radiation efficiency, VSWR, surface current distribution and radiation characteristic. The novel configuration of this design achieves directional radiation pattern maintaining a circularly polarized (CP) radiation characteristics. The measurement result of prototype shows that maximum return loss (RL) of this bow-tie antenna is -28 dB, 4.81 dB realized gain and 6.8 dBi directivity at 2.4 GHz, 1.8 GHz resonating frequencies respectively. The excellent characteristic of wider bandwidths over four resonant frequency bands and high gain of the suggested antenna make it promising candidate for multiple wireless communications as well as energy harvesting system